Autophosphorylation and Cross-Phosphorylation of Protein Kinases from the Crenarchaeon Sulfolobus islandicus - Huang, Qihong; Zhong, Qing; Mayaka, Joseph B. A.; Ni, Jinfeng; Shen, Yulong (Frontiers in Microbiology, 2017)
Protein phosphorylation, one of the most important post-translational modifications, regulates almost every cellular process. Although signal transduction by protein phosphorylation is extensively studied in Eukaryotes and Bacteria, the knowledge of this process in Archaea is greatly lagging behind, especially for Ser/Thr/Tyr phosphorylation by eukaryotic-like protein kinases (ePKs). So far, only a few studies on archaeal ePKs have been reported, most of which focused on the phosphorylation activities in vitro, but their physiological functions and interacting network are still largely unknown. In this study, we systematically investigated the autophosphorylation and cross-phosphorylation activities of ePKs from Sulfolobus islandicus REY15A using proteins expressed in E. coli or S. islandicus. In vitro kinase assay showed that seven out of the eleven putative ePKs have autophosphorylation activity. A protein Ser/Thr phosphatase, SiRe_1009, was able to dephosphorylate various autophosphorylated ePKs, confirming that these proteins are Ser/Thr kinases. Two ePKs, SiRe_2030 and SiRe_2056, homologs of typical eukaryotic PKs involved in peptide synthesis in response to various cellular stresses, exhibit highly efficient phosphorylation activities on both themselves and other ePKs. Overexpression of the protein kinases in vivo revealed that elevated level of either SiRe_1531 or SiRe_2056 inhibited the cell growth of S. islandicus cells. Finally, a phosphorylation network of the protein kinases was proposed and their putative physiological roles were discussed.